Spatial modelling of Cs-137 and Sr-90 fallout after the Fukushima Nuclear Power Plant accident - Bilici, Sevim; Kulahci, Fatih; Bilici, Ahmet (Springer, 2019)
Determination of radionuclides transport characteristics is among the most significant research topics, which require extensive multidisciplinary works. The spatial modeling methods are suggested to determine the effects of radioactive fallout. The spatial analysis has a history of approximately 250 years based on micro-scales, but today it has extended to macroscopic systems. After Fukushima accident, radioactive fallout in water and bottom sediment samples are collected from the deepest tectonic freshwater lake in Turkey, Hazar Lake, and Point Cumulative SemiVariogram and Triple Diagram models are employed for depiction their features. Graphic abstract
Keywords: Geostatistical modelling; Radionuclide transport; Weighting methods; Radioactive fallout; Simulation